2007
DOI: 10.1021/jp072394n
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Electrogenerated Bases in Room-Temperature Ionic Liquids

Abstract: The reductive electrochemistry of substituted benzophenones in the aprotic room-temperature ionic liquid (RTIL) 1-butyl-1-methylpyrrolidinium bistriflimide occurs via two consecutive one-electron processes leading to the radical anion and dianion, respectively. The radical anion exhibited electrochemical reversibility at all time-scales whereas the dianion exhibited reversibility at potential sweep rates of >or=10 V s(-1), collectively indicating the absence of strong ion-paring with the RTIL cation. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
46
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 45 publications
10
46
0
Order By: Relevance
“…This situation is commonly observed for electroactive molecules that can exist as more than one isomer; for example, cis and trans isomers of transition metal complexes, but it is also frequently met by some proteins and other important biomolecules [7,[13][14][15][16][17][18][19]. The features of the SW voltammetric responses in such scenario will significantly depend on the value of the chemical kinetic parameter l, but they will be also affected by the values of the electron transfer kinetic parameters K 1 and K 2 of the two reduction steps.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This situation is commonly observed for electroactive molecules that can exist as more than one isomer; for example, cis and trans isomers of transition metal complexes, but it is also frequently met by some proteins and other important biomolecules [7,[13][14][15][16][17][18][19]. The features of the SW voltammetric responses in such scenario will significantly depend on the value of the chemical kinetic parameter l, but they will be also affected by the values of the electron transfer kinetic parameters K 1 and K 2 of the two reduction steps.…”
Section: Resultsmentioning
confidence: 99%
“…If we consider a surface electron transferchemical reaction (EC) mechanism for example, and if the product of the first electron step can be converted chemically to another electroactive specie, then we assign these reactions to follow the surface electron transfer-chemical reactionelectron transfer (ECE) mechanistic pathway. Although this reaction mechanism is quite complex, it is a widespread pathway of many proteins [7] and other important compounds in organic electrochemistry [1,7,[13][14][15][16][17][18][19]. For example, the product of the first electron transfer step can undergo protonation, elimination, substitution, or reorganization reaction to give second electroactive specie [1,[13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionic liquids (ILs) [11][12][13][14] have emerged as a novel non-aqueous, polar class of solvents that hold great promise in investigations of electrochemical mechanisms [15][16][17][18][19]. The wide electrochemical windows [16,20], intrinsic ion conductivity, high viscosity and hydrophobicity have shown that RTILs are suitable media for supporting reductive processes occurring at very negative potentials allowing stabilization of intermediates in some cases, and improving solubility in others.…”
Section: Introductionmentioning
confidence: 99%
“…At fast scan rates, the initial reduction (radical anion generation) is partially reversible, whereas the second reduction process (dianion generation) is irreversible and shifted anodically, which is a consequence of the protonation of the electrogenerated dianion. However, at low scan rates ( 0.1 V s À1 ), reduction occurs via a two-electron process with the characteristic of an ECE-or DISP1-type mechanism, where the protonation of the radical anion is the rate-determining step via a slow proton-transfer reaction from the [C 4 mim] cation [44]. (Fig.…”
mentioning
confidence: 99%